Transcriptome and functional comparison of primary and immortalized endothelial cells of the human choroid plexus at the blood-cerebrospinal fluid barrier - Denzer, Lea; Muranyi, Walter; Herold, Rosanna; Stump-Guthier, Carolin; Ishikawa, Hiroshi; Sticht, Carsten; Schroten, Horst; Schwerk, Christian; Weichert, Stefan (International journal of molecular sciences, 2025)
The human choroid plexus (CP) is the location of the blood-cerebrospinal fluid (CSF) barrier (BCSFB). Whereas the epithelial cells of the CP mainly contribute to the formation of the BCSFB, the vessels of the CP are built by fenestrated endothelial cells. Still, the CP endothelium can contribute to barrier function. By ectopic expression of human telomerase reverse transcriptase (hTERT) in primary human CP endothelial cells (HCPEnCs), we recently generated and characterized immortalized HCPEnCs (iHCPEnCs). Here, we compared primary cells of the sixth passage (HCPEnCs p6) with a lower (p20) and a higher passage (p50) of iHCPEnCs by transcriptome analysis. A high concordance of HCPEnCs and both passages of iHCPEnCs was observed, as only small proportions of the transcripts examined were significantly altered. Differentially expressed genes (DEGs) were identified and assigned to potentially affected biological processes by gene set enrichment analysis (GSEA). Various components of the endothelial barrier-relevant Wnt signaling were detected in HCPEnCs and iHCPEnCs. Functional analysis of HCPEnCs and iHCPEnCs showed equal marginal activation of Wnt signaling, supporting the downregulation of β-catenin (CTNNB) signaling in CP endothelial cells, and a contribution to the barrier function by the CP endothelium was retained until passage 100 (p100) of iHCPEnCs. Overall, our data support the suitability of iHCPEnCs as an in vitro model of the CP endothelium over extended passages.